Internal marketing dan Marketing strategy: Kajian Literatur - Ameliasari Bartenputri; Yunia Wardi; Susi Evanita; Abror; Vidyarini Dwita (Jurnal Ecogen, 2025)
The purpose of this study is to identify and analyze the relationship between internal marketing and marketing strategy through a systematic literature review (SLR) and bibliometric analysis, focusing on their application in Indonesia using ScienceDirect data from 2020 to 2025. Utilizing PRISMA and VOS viewer, the research narrowed down 105,612 records to 29 relevant articles in business, management, and accounting. Findings highlight that internal marketing, pioneered by Berry in 1981, enhances employee motivation and commitment, thereby strengthening marketing strategies to boost market share, customer loyalty, and competitive advantage. The analysis reveals a strong connection between the two concepts, particularly in fostering organizational culture, market orientation, and brand performance. However, gaps remain, such as the lack of direct measurement of internal marketing’s impact on performance metrics like ROI or customer satisfaction, and limited integration of digital technologies like AI. Notable contributions from researchers like Yonggui Wang (311 citations) emphasize the concepts’ significance, though the low publication count per author suggests a need for more collaborative efforts. The study recommends future empirical research to establish causal links and explore technology’s role in internal marketing, particularly in Indonesia’s service sectors like higher education, to enhance marketing strategies as of now.